MODERN UKRAINIAN LITERARY WORKS ABOUT THE RUSSIAN-UKRAINIAN WAR: ACHIEVEMENT AND LOSSES, IDEAS AND IMPLEMENTATION - Slonovska, Olga (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
Abstract. Modern Ukrainian prose about the Russian-Ukrainian war, which has been going on for almost as long as the Second World War, and is collectively a kind of artistic and thematic meta-formation. His research constitutes the purpose of the article. Both «small» and «large» prose of such thematic specificity have their own genre diversity. Study results. Having considered the problem of covering the war in modern fiction, we prove that all artistic texts can be divided into metagenres. Metagenres (from the Greek meta – through, after, together, together; and the French genere – genus, species) – are types of content-formal unities of artistic works that are commensurate with the entire history of culture. We distinguish three types of metagenres – philosophical, phenomenological and typological as types of modeling of reality by authors. Meditativeness and suggestibility – are the leading and at the same time significant aspects of these models, that is, two ways of understanding and identifying the deep manifestations of people's understanding of the world – mental and intuitive. What is related to analysis and logical reflection is about meditation. And what is expressed by intuition, – belongs to the intuitive understanding of reality, claim literary critics. Practical significance of the research. «Big» and «small» prose with modern themes about war touches on many problems: loyalty and betrayal, patriotism, mentality, gender relations, psychology of a child in war conditions. Ukrainian writers of different generations and different maniftations of their own talents implement their own creative plans. They show the war as a terrible disaster, a test, a kind of test of maturity and humanity. The results of the study of this problem can be used in modern historical and literary publications.